Submarine Groundwater Discharge revealed by radium isotopes (Ra-223 and Ra-224) near a paleochannel on the Southern Brazilian Continental Shelf - Attisano, Karina Kammer (2016)
Submitted by Marcela Polino (marcelapolino15@gmail.com) on 2016-01-02T02:02:58Z No. of bitstreams: 1 a04v61n3.pdf: 257706 bytes, checksum: 63ea41a70249df94c0d1fbc921040415 (MD5)